Tasawuf dan Terapi Krisis Modernisme: Studi Kritis terhadap Pemikiran Seyyed Hossein Nasr - Syamsuri, Syamsuri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2002)
This paper aims to explore Sufism as an alternative solution to the crisis of modernism, particularly in the spiritual domain. It also examines the model or form of Sufism proposed by Seyyed Hossein Nasr as a response to this crisis. By analyzing Nasr’s perspective, this study highlights how Sufism can serve as a counterbalance to the spiritual and existential dilemmas posed by modernity.